THE SEVERITY OF DISCIPLINARY PUNISHMENT AS A REFLECTION OF THE TYPE OF ETHICAL AND PROFESSIONAL INFRACTION IN ACCOUNTING - de Lima, José Ricarte; de Lima, Aparecida de Fátima Alves; da Silva, Elisangela Pires; Coan, Fernanda Mosseline Josende; Manvailer, Ramão Humberto Martins; Pereira, Vanusa Batista (Seven Editora, 2025)
The objective of the present study was to verify whether the type of infraction committed explains the severity of the punishment applied to the accountants. The Declaration of Evidence of Perception of Income (Decore), served as a reference to verify the positive relationship between the type of infraction and the fines applied. To this end, 390 cases carried over in judged in the period from 2014 to 2018 were analyzed against professional accountants with active records in the Regional Accounting Council of the State of Mato Grosso (CRCMT). Logistic regression was used as an econometric approach and power as a strategy in Foucault’s perspective for data analysis. The results showed that there is a positive relationship between the type of infraction and the fines applied to these professionals. The Fines (disciplinary punishment) and warnings (ethical punishment) are the most imposed ethical-disciplinary punishments. The findings of this study the corporate action of the CFC / CRCs system, since these punishments tend to protect the reputation of both the class and the professional. DOI: https://doi.org/10.56238/sevened2025.029-002